Feature tracking cardiovascular magnetic resonance in asymptomatic patients with extracardiac sarcoidosis. (13th July 2021) - Panovsky, R; Doubkova, M; Mojica-Pisciotti, ML; Holecek, T; Machal, J; Feitova, V; Masarova, L; Opatril, L; Kincl, V; Viskova, J
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): European Regional Development Fund - Project ENOCH (No. CZ.02.1.01/0.0/0.0/16_019/0000868) and the Specific University Research (MUNI/A/1685/2020) provided by the Ministry of Education, Youth and Sports of the Czech Republic (MEYS CR) in the year 2020. Introduction: Sarcoidosis is a systemic granulomatous disease affecting many organs including heart. Myocardial strain analysis could potentially detect early stadia of cardiac dysfunction in sarcoidosis patients. Purpose: The study aims to assess use cardiac magnetic resonance (CMR) strain analysis using feature tracking (FT) in the detection of early cardiac involvement in asymptomatic patients with sarcoidosis. Methods: One hundred thirteen CMR studies of patients with extracardiac sarcoidosis without pre-existing known cardiovascular disease were included into the study and analysed using FT and compared to 22 age and gender matched controls. Global longitudinal strain (GLS), global circumferential strain (GCS) and global radial strain (GRS) of left ventricle (LV) were measured. Results: The sarcoidosis patients did not significantly differ from controls in basic demographic data and had normal global and regional systolic LV function – LV ejection fraction (EF) 66 ± 7% vs 65 ± 5% in controls (p = NS). No statistically significant differences were found in all strain parameters between patients and controls: GLS (-13.9 ± 3.1 vs. -14.2 ± 2.5), GCS (-23.4 ± 4.0 vs. -22.2 ± 2.9) and GRS (53.4 ± 13.5 vs. 51.2 ± 13.6%) (p = NS). Conclusion: Asymptomatic patients with extracardiac sarcoidosis had normal myocardial deformation measured by CMR-FT derived global strain.